Editorial - Sofia Oliveira Pais (Market and Competition Law Review)
The Editorial Board is proud to present the first issue of Volume VII of the Market and Competition Law Review. This issue features a number of relevant contributions by several scholars on standard essential patents, FRAND commitments, patent portfolios, and the competition concerns involved.